Revisiting the Role of Exercise Countermeasure on the Regulation of Energy Balance During Space Flight - Laurens, Claire; Simon, Chantal; Vernikos, Joan; Gauquelin-Koch, Guillemette; Blanc, Stéphane; Bergouignan, Audrey (Frontiers in Physiology, 2019)
A body mass loss has been consistently observed in astronauts. This loss is of medical concern since energy deficit can exacerbate some of the deleterious physiological changes observed during space flight including cardiovascular deconditioning, bone density, muscle mass and strength losses, impaired exercise capacity, and immune deficiency among others. These may jeopardize crew health and performance, a healthy return to Earth and mission’s overall success. In the context of planning for planetary exploration, achieving energy balance during long term space flights becomes a research and operational priority. The regulation of energy balance and its components in current longer duration missions in space must be re-examined and fully understood. The purpose of this review is to summarize current understanding of how energy intake, energy expenditure and hence energy balance are regulated in space compared to Earth. Data obtained in both actual and simulated microgravity thus far suggest that the obligatory exercise countermeasures program, rather than the microgravity per se, may be partly responsible for the chronic weight loss in space. Little is known of the energy intake, expenditure and balance during the intense extravehicular activities which will become increasingly more frequent and difficult. The study of the impact of exercise on energy balance in space also provides further insights on lifestyle modalities such as intensity and frequency of exercise, metabolism, and the regulation of body weight on Earth, which is currently a topic of animated debate in the field of energy and obesity research. While not dismissing the significance of exercise as a countermeasure during space flight, data now challenge the current exercise countermeasure program promoted and adopted for many years by all the International Space Agencies. An alternative exercise approach that has a minimum impact on total energy expenditure in space, while preventing muscle mass loss and other physiological changes, is needed in order to better understand the in-flight regulation of energy balance and estimate daily energy requirements. A large body of data generated on Earth suggests that alternate approaches, such as high intensity interval training (HIIT), in combination or not with sessions of resistive exercise, might fulfill such needs.